Pendidikan Karakter Anak Usia Dini Melalui Kegiatan Kepramukaan Di SDN Karanggintung 01 Dan SDN Karanggintung 02 Kecamatan Gandrungmangu - Rama Cipta Prasetia; Kuat Leksono; Alwi Fauji (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2025)
This scouting activity will go through several stages until in the end the students receive the character education referred to by the author. The first stage is basic, namely an introduction to the history of "World Scouts and Scouts in Indonesia." By getting to know the history of scouting, it is hoped that students will be more interested and enthusiastic in taking part in the next activities. The expected character education is high curiosity. The second stage, began to introduce some scouting materials such as Box 1 Password and Semaphore. On the other hand, there is a replacement program, namely Scouting Extracurricular Activity Training with the majority of participants being students from SD Negeri Karanggintung 01 and 02. This program is held every Wednesday and Friday or can be adjusted to unexpected situations and conditions. The Scouting Program continues to be successfully implemented and of course cannot be separated from the help of several related parties. The author even implemented a calligraphy training program to develop and foster interest in the talents of elementary school age children.